NORMATIVITY IN LEGAL SOCIOLOGY: Methodological Reflection on Law and Regulation in Late Modernity - Hermawan, Sapto; Surya Kusuma, Febrian Indar (Yustisia, 2022)
Debates on the discussion of the law limits began to emerge along with the development of science. For some circles, interdisciplinary discussions are considered essential because they can complement a mature legal study. This concept also gave rise to legal studies carried out together with other scientific groups such as social sciences. In this context, the combination of the scope of social science and law has contributed to studying the prevailing social conditions by applying the rule of law. The limitations of the extra-legal aspects that appear in the socio-legal study are what then raise and require confirmation to be said as a study that results from the legal study space.